Solution Processed Semiconducting Nanosheet Networks Towards Optoelectronic Applications - Liu, Shixin (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
Two-dimensional (2D) semiconducting transition metal chalcogenides (TMDs) are attractive materials owing to their superb electronic and optoelectronic properties. The great advancement of material exfoliation and thin film fabrication methods over the past years allows these 2D materials to be solution-processed into nanosheet networks, serving as basic electronic components. In this thesis, to fully reveal their potential, these 2D networks will be integrated with other low-dimensional materials, forming novel device structures towards optoelectronic applications. The device structure determines their electrical behaviors. To test this, vertically metal-semiconductor-metal (MSM) devices were fabricated using liquid exfoliated semiconducting tungsten disulfide (WS2) nanosheets and one-dimensional metallic nanomaterials as electrodes, such as single-walled carbon nanotubes (SWNTs). Electrical short-free vertical heterostructures, down to a WS2 film thickness ~0.5 ?m, were realized. By performing the electrical measurements, the obtained devices displayed bulk-limited conduction behaviors when SWNTs were dispersed in isopropanol. The out-of-plane conductivity and mobility were extracted to be ~1.63?10-4 S m-1 and ~5.36?10-3 cm2 V-1 s-1, respectively, which were around 1 order of magnitude lower than their in-plane values. When SWNTs were dispersed in a surfactant aqueous solution, the surfactant induced doping effect to the semiconducting nanosheet networks and resulted in electrode-limited Schottky behaviors at the SWNTs/ WS2 interfaces. Furthermore, by increasing the WS2 film thickness, a transition from electrode- to bulk-limited electrical behavior was observed with a critical transition film thickness of ~2.6 ?m. The porous and rough nanosheet networks could also be covered with a thin film semiconductor to avoid the electrical shorts and form heterojunctions at this semiconductor-semiconductor interface. Using ZnO nanoparticles and PEDOT:PSS as carrier transport layers, vertically stacked heterojunctions were successfully fabricated with liquid exfoliated tungsten diselenide (WSe2) nanosheets. Due to the improved energy band alignment at the interface, the heterojunctions exhibited a high rectification ratio ~104 at ?1 V, which is the highest among solution-processed heterojunctions using liquid exfoliated nanosheets without relying on the heavily doped silicon. The devices could be used as self-powered photodetectors in both photoconductor and photodiode modes under AM 1.5D illumination. The photoresponsivity at 1 V was ~1.5 A W-1 which is highest for photodetectors based on solution-processed WSe2 nanosheets. The interface properties play a vital role in the performance of heterojunction devices. Therefore, the interfacial behaviors of the liquid exfoliated WSe2 nanosheet network were manipulated by sandwiching it between various types of transport layers, such as ZnO, TiO2, and NiO, etc. The photovoltaic performances of these devices were tested under AM 1.5D illumination. The devices displayed distinctive electrical behaviors with short-circuit current densities ranging from 1.32?10-3 to 2.50 A m-2 and open circuit voltages from 4 to 242 mV, but a rather low fill factor around 20-27%. The highest efficiency was obtained to be 1.95?10-3 % when ZnO and NiO were used as transport layers. The low short circuit current density is identified to be the main limiting factor for the poor photovoltaic performance and further improvements will be required. The van der Waals (vdW) heterojunction formed with two types of semiconducting TMDs nanosheets are expected to exhibit a better performance where the interface is constructed with dangling bonds-free surfaces. Using electrochemically exfoliated (EE) nanosheets, conformal and lateral nanosheet alignment could be realized due to their atomic thin thicknesses and large aspect ratios. The vdW heterojunctions were successfully fabricated with EE WS2 and niobium doped WSe2. The electrical measurements showed that the vdW heterojunction could form a broken-gap type heterojunction that induces band-to-band tunneling behaviors. The device was further measured under 1000 W m-2 AM 1.5D illumination, and photoresponsivity of 0.13 and 0.14 A W-1 were obtained at -1 V and 1 V, respectively.
APPROVED
Keywords: Transition metal dichalcogenides; Solution processing; Optoelectronics; 2D materials